Вплив нековалентного модифікування на структурні характеристики багатошарових вуглецевих нанотрубок - Kowalska, E. A.; Brichka, S. Ya.; Kartel, M. T.; Yanchuk, I. B.; Matolin, V.; Vorokhta, M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
The influence of noncovalent modifications on structural characteristics of the commercial multiwall carbon nanotubes has been studied. The modification was provided by decoration of cerium nanoparticles from aqueous solutions. The structural characteristics of samples of carbon nanotubes were studied by methods of transmission, Raman, and X-ray spectroscopy.